2009
DOI: 10.1002/ejic.200900513
|View full text |Cite
|
Sign up to set email alerts
|

DFT Study of Small Palladium Clusters Pdn and Their Interaction with a CO Ligand (n = 1–9)

Abstract: This paper presents a theoretical study of palladium clusters Pd n of low nuclearity, ranging from 1 to 9, completed by their interactions with a carbonyl ligand (Pd n CO). The simulations were performed at the DFT (B3LYP-Lanl2DZ) level. Small palladium clusters are deltahedral structures characterized by a triplet ground state (Pd 2 to Pd 7 ) or a quintet ground state for larger nuclearities (Pd 8 and Pd 9 ). Various electronic states relatively close in energy are present. These states have close geometries … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
36
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 37 publications
7
36
0
1
Order By: Relevance
“…The PW91PW91 results indicated that Ag clusters bind CO only on top site while Pd 2 binds CO on bridge site and both Pd 3 and Pd 4 bind CO on 3-fold face site, which agrees well with previous reports [5][6][7][8]11]. For alloying dimer, it is found that CO prefers binding on top-Pd site with the C-Pd-Ag angle of 106.6°.…”
Section: Structures and Stabilitysupporting
confidence: 90%
See 1 more Smart Citation
“…The PW91PW91 results indicated that Ag clusters bind CO only on top site while Pd 2 binds CO on bridge site and both Pd 3 and Pd 4 bind CO on 3-fold face site, which agrees well with previous reports [5][6][7][8]11]. For alloying dimer, it is found that CO prefers binding on top-Pd site with the C-Pd-Ag angle of 106.6°.…”
Section: Structures and Stabilitysupporting
confidence: 90%
“…As one of the key factors to understand the catalytic mechanism, the adsorption behavior of CO on Pd clusters has been extensively studied [5][6][7][8][9][10]. The infrared multiple photo dissociation (IR-MPD) spectroscopy studies on CO adsorption on group 10 (Ni, Pd, Pt) clusters has showed that both Ni and Pt clusters adsorb CO only in atop positions while Pd clusters exhibit a variety of binding sites [5].…”
Section: Introductionmentioning
confidence: 99%
“…B. Pd 0 -Verbindungen relativ elektronenarm und erschwert somit die oxidative Addition von Organohalogenverbindungen an die Pd 0 -Spezies. [9] Infolgedessen sind normalerweise strenge Reaktionsbedingungen wie z. B. hohe Temperaturen und hoher CO-Druck nçtig (siehe Schema 1, Pfad A).…”
Section: Introductionunclassified
“…In this work, the oxidative addition of organohalides to Pd(0) takes place firstly followed by coordination and insertion of CO, and finally reductive elimination occurs giving the carbonylated product. However, the π acidity of CO renders the CO-coordinated low-valence metal electron deficient, which makes oxidative addition of organohalides to Pd(0) difficult [28]. As a result, harsh conditions are often required for this kind of carbonylation.…”
mentioning
confidence: 99%